2021
DOI: 10.46747/cfp.6706427
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent epistaxis in children

Abstract: Question A child came to my clinic complaining of recurrent epistaxis with several episodes occurring every year since he was a toddler. The nosebleeds affect both nostrils, often lasting for an extended period of time and occurring in no apparent seasonal pattern. What interventions are safe and effective for recurrent epistaxis in children, and which patients warrant hematologic testing? Answer Epistaxis affects more than half of children by the time they are 10 years old, with 9% of children reported to hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 22 publications
1
30
0
3
Order By: Relevance
“…All children hospitalized during the 1-year period that fulfilled the inclusion criteria were included in the study. Inclusion criteria for the study were; (1) >1 month and ≤18 years old; (2) receiving antibiotics during hospitalization; (3) having no comorbid diseases such as cystic fibrosis, inflammatory bowel disease, celiac disease, allergic diseases, immunodeficiencies, chronic renal failure, diabetes, intestinal parasites and other chronic diseases that may be associated with increased risk of diarrhea and (4) absence of acute gastroenteritis at initial admission; and no usage of drugs such as probiotics, prebiotics, laxatives, and anti-diarrheal drugs within the previous 2 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All children hospitalized during the 1-year period that fulfilled the inclusion criteria were included in the study. Inclusion criteria for the study were; (1) >1 month and ≤18 years old; (2) receiving antibiotics during hospitalization; (3) having no comorbid diseases such as cystic fibrosis, inflammatory bowel disease, celiac disease, allergic diseases, immunodeficiencies, chronic renal failure, diabetes, intestinal parasites and other chronic diseases that may be associated with increased risk of diarrhea and (4) absence of acute gastroenteritis at initial admission; and no usage of drugs such as probiotics, prebiotics, laxatives, and anti-diarrheal drugs within the previous 2 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…1 Most guidelines recommend preventing AAD in high-risk patients by using specific strains of probiotics along with antibiotic treatment. 2–4…”
mentioning
confidence: 99%
“…The precise incidence is unclear, but it is suggested that as many as three in four children may experience at least one episode of epistaxis at some time. Recurrent epistaxis is seen in 9% of children and it is a common cause of presentation to emergency departments 8–10…”
Section: Introductionmentioning
confidence: 99%
“…Health care providers frequently treat nosebleeds, and epistaxis has been the subject of many contemporary reviews (Krulewitz & Fix, 2019; Schlosser, 2009; Tunkel et al, 2020; Womack et al, 2018; Yau, 2015; Qureshi 2012). The American Academy of Otolaryngology—Head and Neck Surgery recently published clinical epistaxis guidelines (AAOHNS Guidelines) (Tunkel et al, 2020).…”
Section: Introductionmentioning
confidence: 99%